2007
DOI: 10.1007/s11274-007-9414-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physiological alterations occurring in a yeast population continuously propagated at increasing temperatures with cell recycling

Abstract: This work investigated the effects of increasing temperature from 30°C to 47°C on the physiological and genetic characteristics of Saccharomyces cerevisiae strain 63M after continuous fermentation with cell recycling in a system of five reactors in series. Steady state was attained at 30°C, and then the temperature of the system was raised so it ranged from 35°C in the last reactor to 43°C in the first reactor or feeding reactor with a 2°C difference between reactors. After 15 days at steady state, the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…As yeast strains tolerant to high temperatures can be of great value for biotechnological applications, it was decided to identify the elongated cells that were sporadically proliferating within a continuous fermentation system when temperatures as high as 39-47°C were reached within the bioreactors [34]. Based on this, it was concluded that this continuous system was capable of enriching its culture with yeasts able to grow at temperatures higher than those tolerated by conventional strains of S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As yeast strains tolerant to high temperatures can be of great value for biotechnological applications, it was decided to identify the elongated cells that were sporadically proliferating within a continuous fermentation system when temperatures as high as 39-47°C were reached within the bioreactors [34]. Based on this, it was concluded that this continuous system was capable of enriching its culture with yeasts able to grow at temperatures higher than those tolerated by conventional strains of S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…Starter strain 63 M of Saccharomyces was the predominant isolate within the same fermentation system when operated at increasing temperatures. Due to the increasing temperatures, a great diversity of variants made up of haploid cells and recombinant and mutant strains of S. cerevisiae were obtained from this system [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many studies of the genetics of S. cerevisiae strains that are involved in the fermentation process for the production of wine (Blanco et al 2006;Nikolaou et al 2007;Vaudano and Garcia-Moruno 2008). Several molecular methods for identification of yeast strains, such as analysis of mitochondrial DNA (Fernández-Espinar et al 2001;Mercado et al 2007), karyotyping by pulsedfield gel electrophoresis (PFGE) (Cocolin et al 2004;Souza et al 2007;) and fingerprinting based on the repetitive delta sequences (Schüller et al 2004), have demonstrated a great deal of genetic diversity in oenological strains of S. cerevisiae (Nikolaou et al 2007), which is affected by factors that include geographical location (Guillamón et al 1996), technology used (Epifanio et al 1999) and temperature of fermentation (Fleet and Heard 1993;Vaudano and Garcia-Moruno 2008).…”
Section: Introductionmentioning
confidence: 99%